Bridging the Digital Divide: Enhancing Teacher Competencies for Student-Centered Learning Through Microsite Development - Dewi, Atika Ratna; Yuniati, Trihastuti; Arifa, Amalia Beladinna; Sari, Dian Kartika; Alika, Shintia Dwi (Edumedia Solution, 2026)
Elementary school teachers at Tumiyang 1 Public Elementary School face significant challenges in adopting digital technology effectively with 73% having no prior knowledge of microsites and limited skills in creating interactive digital learning media. This digital literacy gap, common in rural educational contexts, results in conventional teaching methods that fail to engage today’s digital generation effectively. To address these challenges, a two-day intensive microsite creation training program was implemented using a participatory approach through hands-on training, mentoring, and product-based evaluation. The program consisted of three main stages, preparation, implementation, and evaluation and monitoring. Teachers learned to create web-based learning media using Google Sites and S.Id, integrating various digital resources, including Google Drive, Google Forms, YouTube, and Canva. Post-training evaluation revealed universally positive outcomes that most of the participants gained understanding of microsites, with all teachers successfully creating functional, content-rich microsites tailored to their subject areas. All participants expressed interest in further learning and rated the training as effective with clear and accessible materials. This program successfully bridged the digital competence divide, empowering rural teachers as agents of change capable of creating adaptive, interactive learning environments and contributing to educational equity between urban and rural areas.